Designing effective instruction - Morrison, Gary R.; Ross, Steven M.; Kemp, Jerrold E. (Hoboken, NJ : J. Wiley, 2007)
"This valuable resource provides instructional designers with the guidance they need to meet the challenge of creating effective and efficient instruction. Maintaining a careful balance between theory and application, the Fourth Edition presents a practical, easy-to-follow approach to instructional design that can be applied to K-12 classrooms, higher education, distance education, and business programs. The authors incorporate behavioral and cognitive approaches into their model, so that readers can reap the benefits of both.
Includes bibliographical references and index.
Keywords: Instructional systems -- Design; Curriculum planning